2013
DOI: 10.3892/mmr.2013.1459
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of essential oils from Chamaecyparis obtusa via the cyclooxygenase-2 pathway in rats

Abstract: Abstract. Essential oils are concentrated hydrophobic liquids containing volatile aromatic compounds from plants. In the present study, the essential oil of Chamaecyparis obtusa (C. obtusa), which is commercially used in soap, toothpaste and cosmetics, was extracted. Essential oil extracted from C. obtusa contains several types of terpenes, which have been shown to have anti-oxidative and anti-inflammatory effects. In the present study, we examined the anti-inflammatory effects of C. obtusa essential oil in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…This oil showed anti-inflammatory effects regulating the production of PGE2 enzyme in the blood and the gene expression of TNF-α in rats. Such effects are mediated by the inhibition of the expression of the inflammation-specific COX-2 enzyme (An et al, 2013). Another study analyzed the anti-inflammatory atopic activity of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This oil showed anti-inflammatory effects regulating the production of PGE2 enzyme in the blood and the gene expression of TNF-α in rats. Such effects are mediated by the inhibition of the expression of the inflammation-specific COX-2 enzyme (An et al, 2013). Another study analyzed the anti-inflammatory atopic activity of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction process facilitates the collection of volatile oils from the processing material. Volatile oils reduce acute and chronic inflammation and, more importantly, facilitate the absorption of other bioactive compounds in humans (18). Compounds obtained by supercritical fluid extraction are very stable and can be used directly in experimental diet supplementation (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of plant extracts on wound healing and skin barrier function in skin disorders have been documented (Mantle et al, 2001;Reuter et al, 2010). Researchers have shown that whole plant oils from Chamaecyparis obtusa have anti-inflammatory effects and are not cytotoxic (An et al, 2013;Chien et al, 2014). However, bactericidal activities and wound-healing properties of the C. obtusa extract have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%